The basic principles of immunosuppressive therapy after kidney transplantation - D. N. Suslov (Трансплантология (Москва), 2018)
The article deals with medical and organizational issues of individually-adapted immunosuppressive therapy in renal allograft recipients. In the recent years, the basis of nephroprotective therapy schemes includes m-TOR inhibitors. The accessibility of these drugs for those in need is limited. Meanwhile, a more widespread use of these drugs in clinical transplantation would both increase the life span of a transplanted kidney, and reduce the risk of viral infections and cancer in the long-term after kidney transplantation, and would also allow a rational use of budget funds for the treatment of such patients.